The Implementation of Ruqyatul Hilal in the Shafi'i Scholars' Texts - , Ahmad Ash Shonhaji (Sufiya Journal of Islamic Studies, 2024)
The purpose of this study is to explain the method of ruqyah hilal in Indonesia. This study uses a qualitative method with a content analysis approach. Primary and secondary data were obtained from the books of Shafi'iyah scholars. The results of the study show that the ruqyah hilal method applied in Indonesia has a strong foundation in the Islamic scientific tradition, especially in the Shafi'i madhhab. This study also identifies various approaches used by scholars in determining the beginning of the hijri month based on the observation of the hilal, as well as the contribution of this methodology to religious practices in Indonesia. However, the weakness of this method is the dependence on weather conditions that often hinder the accurate observation of the new moon, as well as differences in interpretation among scholars that can cause inconsistencies in determining the beginning of the month in various regions. This can lead to uncertainty and differences in the implementation of worship that depend on the determination of a certain time.